SCREENING DISFAGIA DENGAN INSTRUMENT STANDARDIZED SWALLOWING ASSESSMENT PADA PASIEN DENGAN GANGGUAN NEUROLOGI DI RSUP DR. WAHIDIN SUDIROHUSODO - Asri, Indra Junsen; Rosnia, Rosnia; Hidayat, Rahmat; Sjattar, Elly L; Afelya, Titi Iswanti (Universitas Islam Negeri Alauddin Makassar, 2019)
Screening of Dysphagia is one of the applications of Evidence Based Nursing (EBN) to reduce complications. From the results of the study found that Screening Dysphagia can be effectively carried out by nurses and cause a decrease in the level of pneumonia (Palli et al., 2017). Screening of Dysphagia also reduces the level of bronchoaspiration in acute stroke patients (Cocho et al., 2015). Many instruments that can be used in Screening of Dysphagia. The best instruments are used with top sensitivity and specificity and evaluation of the results of methodological quality evaluations with a 12 steps criterion adapted from (Jaeschke et al) Namely the Standarized Swallowing Assessment (SSA) instrument. The purpose of this EBN is to assess the effective, efficient and safe use of SSA instruments and the prevalence of dysphagia in dysphagia screening in the lontara neuro treatment room 3 floors 1 behind RSUP Dr. Wahidin SudirohusodoMakassar. In implementing this EBN, it was found that Dysphagia Screening using SSA instruments was effective, efficient and safe to use. Of the 19 patients, 6 were found to have dysphagia.